Retention of Employees in the Manufacturing Company - A Case Study - Nagesh, P.; Sherif, Aisha M. (Prabandhan: Indian Journal of Management, 2010)
Human resource management involves employing the people, developing their resources, utilizing, maintaining and compensating their services in tune with the job and organizational requirements with a view to contribute to the goals of the organization, individual and the society. Human resource management is concerned with the development of human resource, i.e. knowledge, capacity, skills, potentialities and attaining & achieving employee goals, including job satisfaction of employees from all levels and categories (unskilled, professional, clerical and managerial). Therefore, human resource management includes, all those activities starting from human resource planning, up to the employee retention. The challenges in people management in any organization are, 1. Attracting, developing and retaining the right talent work source which is necessary for the productive work force. 2. Developing the way to forecast to know the workers needs. 3. Understanding the workforce agility. Among the above, employees retention in today’s contemporary business is really a changing job to the leader organizations [1].The key to retaining productive employees is making their environment as conductive as possible to the achievement of the company’s business goals and objectives. To design the appropriate retention program, companies should take the step and try to access the relationship the company has with its individual employees and how they perceive their relationship with the company.